Pengaruh Pemberian Jenis Pakan Yang Berbeda Terhadap Kelangsungan Hidup Dan Pertumbuhan Larva Ikan Gabus (Channa striata) - Yulintine Yulintine; Maryani Maryani; Herma S Siburian (Universitas Batangahari Jambi, 2023)
The purpose of this study was to determine the effect of different feeding on the survival rate and growth of snakehead fish (Channa striata) larvae. This research was conducted using a completely randomized design (CRD) with 3 treatments and 3 replications. The treatment consisted of treatment A treatment with artificial feeding PF 0, treatment B with feeding Daphnia and treatment C with feeding silk worms. The results showed that the provision of different types of feed had a significant effect on survival, absolute weight growth, daily weight growth rate, absolute length growth rate, daily length growth rate and feed conversion of snakehead fish larvae (Channa striata). The best feeding for the survival and growth of snakehead fish larvae is found in feeding using natural feed silk worms and Daphnia sp.